EFFECT OF BIOFERTILIZER, TECAMIN MAX AND BENZYL ADENINE ON LEAVES MINERALS OF SWEET ORANGE SEEDLINGS - A. S. Abdulrhman,; S. M. Al-Atrushy, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research was aimed to study the effect of soil application of Bio health and foliar application with Tecamin max and Benzyl adenine on leaves minerals content of sweet orange (Citrus sinensis L.) seedlings during two successive seasons (2020 and 2021) using Randomized Complete Design with four replications. Bio health was added with three concentrations (0, 6 and 12 g.L-1) to the soil and foliar application of Tecamin max with three concentration (0, 5 and 10 ml.L-1) and Benzyl adenine with three concentration (0, 100 and 200 mg. L-1) on the sweet orange seedlings which were brought from private nursery in Duhok city and have two- years old and almost uniform in growth vigor. The results showed that all parameters such as, N, P, K, Ca and Fe leaves content in both seasons were increased significantly as compared with control, accept proline and Na was significantly decreased with increasing application of the bio-health, Tecamin max and Benzyl adenine, Furthermore, combination among high concentration of Bio health, Tecamin max and Benzyl adenine improved all parameters in comparison with the control.